Neratinib could be effective as monotherapy or in combination with trastuzumab in HER2-low breast cancer cells and organoid models - Arshad, M; Azad, A; Chan, PYK; Vigneswara, V; Feldinger, K; Nafi, SNM; Laporte-Maguire, E; De Santo, C; Zuo, J; Shaaban, AM; Kong, A (Springer Nature [academic journals on nature.com], 2024)
Background: Previous studies have suggested that patients with HER2-low breast cancers do not benefit from trastuzumab treatment although the reasons remain unclear. Methods: We investigated the effect of trastuzumab monotherapy and its combination with different HER2 targeting treatments in a panel of breast cancer cell lines and patient-derived organoids (PDOs) using biochemical methods and cell viability assays. Results: Compared to sensitive HER2 over-expressing (IHC3 + ) breast cancer cells, increasing doses of trastuzumab could not achieve IC50 in MDA-MB-361 (IHC 2 + FISH + ) and MDA-MB-453 (IHC 2 + FISH-) cells which showed an intermediate response to trastuzumab. Trastuzumab treatment induced upregulation of HER ligand release, resulting in the activation of HER receptors in these cells, which could account for their trastuzumab insensitivity. Adding a dual ADAM10/17 inhibitor to inhibit the shedding of HER ligands in combination with trastuzumab only showed a modest decrease in the cell viability of HER2-low breast cancer cells and PDOs. However, the panHER inhibitor neratinib was an effective monotherapy in HER2-low breast cancer cells and PDOs, and showed additive effects when combined with trastuzumab. Conclusion: This study demonstrates that neratinib in combination with trastuzumab may be effective in a subset of HER2-low breast cancers although further validation is required in a larger panel of PDOs and in future clinical studies.